1988
DOI: 10.1037/0882-7974.3.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Sustained attention in adulthood: A unique, large-sample, longitudinal and multicohort analysis using the Mackworth Clock-Test.

Abstract: A cross-sectional sample of men (n = 177) tested in 1962-1964, and men (n = 188) and women (n = 113) tested in 1980-1984, and a longitudinal sample (n = 53) of men tested in 1962-1964 and 1980-1984, were used to investigate age differences and 18-year age changes on a 62-min sensory vigilance task that made virtually no demand on memory, the Mackworth Clock-Test. Age differences and changes in the vigilance decrement were also examined. No age differences or changes were obtained for detection accuracy. Target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1

Year Published

1988
1988
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 7 publications
2
39
1
Order By: Relevance
“…A. Rogers, 2000). One very large-scale study using a vigilance task-the Mackworth Clock Task-failed to find any evidence of sustained-attention deficits in older adults (Giambra & Quilter, 1988). It is possible that the increased sensitivity of the SART in comparison to vigilance tasks enabled it to detect age-related decline in this study.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…A. Rogers, 2000). One very large-scale study using a vigilance task-the Mackworth Clock Task-failed to find any evidence of sustained-attention deficits in older adults (Giambra & Quilter, 1988). It is possible that the increased sensitivity of the SART in comparison to vigilance tasks enabled it to detect age-related decline in this study.…”
Section: Discussionmentioning
confidence: 75%
“…A. Rogers, 2000). One very large-scale study, involving over 500 participants from the ages of 18 to 91, found little evidence of any age-related decrement in sustained attention ability, as measured by the Mackworth Clock Test, a 62-min sensory vigilance task (Giambra & Quilter, 1988). Studies of the selectivity aspect of attention have employed visual search tasks (Treisman & Gelade, 1980) and visuospatial orienting tasks (Posner, 1980).…”
mentioning
confidence: 99%
“…Reaction time is the latency between critical signal onset and the participant's 1991; Edley & Knopf, 1987). Performance also is usually poorer among participants with clinical diagnoses of schizophrenia, ADHD, learning disability, brain injury, dementia, depression, and anxiety (Beale, Matthew, Oliver, & Corballis, 1987;Chee, Logan, Schachar, Lindsay, & Wachsmuth, 1989;Earle-Boyer, Serper, Davidson, & Harvey, 1991;Goetsch & Adams, 1990;Kaufmann, Fletcher, Levin, Miner, & Ewing-Cobbs, 1993;Mirsky, et al, 1992;Parasuraman, Mutter, & Molloy, 1991).…”
Section: The Traditional Continuous Performance Test (Cpt)mentioning
confidence: 99%
“…Since then several studies have found evidence of age differences (e.g., Bunce, Barrowclough & Morris, 1996;Giambra, 1997;Parasuraman, Nestor, & Greenwood, 1989;Parasuraman & Giambra, 1991), although others (e.g. Giambra & Quilter, 1988) have not. Research examining age differences in the vigilance decrement is also inconsistent.…”
Section: Introductionmentioning
confidence: 99%